Przekonania nauczycieli o potencjale uczenia się dziecka w młodszym wieku szkolnym - Kochanowska, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
One of the main factors determining the approach of teachers to development of learning potential of a child is the way of a child’s understanding and beliefs of teachers about the opportunities and ways of its development. The following study aims to present beliefs and opinions of teachers about learning potential of children at early school age and opportunities of its development, obtained by analyzing speech given by teachers during narrative interviews conducted with them within the study. Teachers’ beliefs with regard to learning potential of a child affect the way of planning and conduct of the educational process and, consequently, a change in the personalities of the students. Hence there occurs a need for verification, especially teachers’ misconceptions concerning the issue discussed within the article.
Keywords: child at early school age; learning potential; teachers’ beliefs